The Handy Eye Chart(™): A New Visual Acuity Test for Use in Children - Cromelin, Caroline H. (2012)
OBJECTIVE: To design a simple matching acuity test based on hand gestures that is minimally dependent on familiarity with symbols and letters. The visual acuity results obtained from children using the Handy Eye Chart(™) were compared with results obtained with the Early Treatment Diabetic Retinopathy Study (ETDRS) chart. DESIGN: Evaluation of diagnostic test or technology. PARTICIPANTS: 60 children between 6 and 16 years of age were recruited consecutively from the Pediatric Ophthalmology section of the Emory Eye Center. METHODS: Monocular visual acuity was tested using both the new eye chart and the ETDRS chart, alternating the order of administration between subjects. Testing was performed on the subject’s eye with the poorest acuity. MAIN OUTCOME MEASURES: Outcome measures were monocular logarithm of the minimum angle of resolution (logMAR) visual acuity scores for each chart. RESULTS: The acuities were shown to have a strong linear correlation (r = 0.95) and a mean difference in acuity of −0.03 (95% confidence interval −0.05 to −0.01) logMAR, equivalent to approximately 1.5 letters, with the new eye chart underestimating the vision as determined by the ETDRS chart. The 95% limits of agreement were ±1.6 lines. CONCLUSION: The present study supports the validity of the new eye chart as a measure of visual acuity in pediatric patients ages 6 to 18 with vision ranging from 20/16 to 20/200.